Sjæleøje-Stavnen eller Sjæle-Færge-Stavnen? En tesktkritisk drøftelse - Lundgreen-Nielsen, Flemming (Grundtvig-studier, 1994)
Soul-Eye-Prow or Soul-Ferry-Prow?By Flemming Lundgreen-Nielsen Grundtvig’s last completed poem .Old Enough I Now Have Grown. (1872) in stanza 3 presents a word that has not as of yet been deciphered with absolute certainty. At the first publication of the poem in 1880 by his son Svend it was given as » Sjæleøje-Stavnen« (literally: Soul-Eye-Prow), from 1964 on the reading .Sj.le-Færge-Stavnen. (literally: Soul-Ferry-Prow) has been suggested. The paper endeavours to settle this philological dispute. Firstly various renditions of the word through more than one century’s prints and reprints are registered, with specific regard to the (neglected) accuracy of spelling. Secondly the possible reading Soul-Eye- is verified as part of the metaphors of Danish Romanticism (found in B.S. Ingemann and in a hymn by Grundtvig), but due to lack of logical and metaphorical coherence the combination of the concrete word eye and the equally concrete word prow is rejected as against Grundtvig’s general practice in creating compounds.Contrarily Soul-Ferry- does make fine sense as part of an image of Charon’s boat and effortlessly combines with Prow. Thirdly the actual characters and strokes in the relevant line of Grundtvig’s manuscript are examined in minute details. The main problem is that Grundtvig because of failing eye-sight sometimes wrote words or letters with his steel pen without realising that he had run out of ink. The final result of this examination implies that the reading »Færge« (Ferry) seems the only possible one considering the number and kind of letters between the hyphens in the middle constituent of the trinomial compound. It is mentioned that in a scrutiny the small-scale photographic reproduction of the manuscript in Grundtvig’s Sang-Værk, vol. 6, 1964, cannot serve as a substitute for Grundtvig’s manuscript (in the Grundtvig Archive, The Royal Library, Copenhagen); neither can a contemporary handwritten copy.